(untitled) (KYAMC Journal, 2023)
Background: The distribution of diseases in society varies across communities and geographical places. Diseases of the ear, nose, and throat (ENT) pose severe public health issues in both rural and urban populations. Objective: To determine the demographic disease pattern in the ENT and Head and Neck Surgery (HNS) Out Patient Department (OPD). Materials and Methods: This retrospective study is based on patient’s medical records who attended the Out Patient Department of Otorhinolaryngology, Khwaja Yunus Ali Medical College and Hospital (KYAMCH). The study records covered 2312 patients who visited the Out Patient Department from September 2019 to August 2020 were included in this study. Results: Study of patients in light of their diagnoses of chronic tonsillitis in 367 (15.87%), followed by chronic pharyngitis affected 347 (15.01%) patients, allergic rhinitis in 135 (5.74%), acute/chronic adenotonsillitis with otitis media with effusion in 133 (5.75%), and otitis externa in 123 (5.32%) individuals. In a broad heading, if the tonsils are mainly affected, it’s called tonsillitis; if the throat is mainly affected, it’s called pharyngitis. Conclusion: High prevalence of chronic tonsillitis and pharyngitis among ENT illnesses. The most prevalent ENT conditions include chronic suppurative otitis media (CSOM/COM) 11.63%, allergic rhinitis, acute and chronic adenotonsillitis, otitis media with effusion (OME), otitis externa and acute tonsillitis. KYAMC Journal Vol. 14, No. 01, April 2023: 43-47